Microeconomics in active pedagogy applied to the African contexte - (:unkn) unknown (My University, 2025)
This work aims to enhance and share our experience of higher education, our daily curiosity and observation of economic facts and practices, and our strong sense of justice. To this end, several points of attention on the dimension of economic analysis, the concept of opportunity cost or opportunity cost, the inversion of demand and supply functions, the subtleties in the calculation and interpretation of elasticities and the marginal rate of substitution were among others addressed to clear up equivocations among students. Aspects of moral analysis and cheating practices in economics were also discussed.
Keywords: African Research